The effectiveness of third party release in cross-border cases - Torralba Mendiola, Elisa (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Article 652.2 of the Insolvency Act provides that the effects of the restructuring plan of a group company can be extended to personal or in rem guarantees provided by any other company of the same group not subject to the restructuring plan, when the enforcement of the guarantee may cause the insolvency of the guarantor and the debtor itself. A similar rule is contained in Article 596.3 of the same Law for cases of notification of the opening of negotiations. The effectiveness of these rules is called into question in cross-border situations, in which the provisions of the European Union and/or the rules on recognition of the country in which recognition is to take place may establish certain obstacles, derived fundamentally from their understanding of the extent of the jurisdiction of the Spanish authorities. Although the Insolvency Act allows the effectiveness of the aforementioned articles to be saved in certain situations, it does not guarantee it in all cases.